Scalable Synthesis of Self‐Disinfecting Polycationic Coatings for Hospital Relevant Surfaces - Samuel Watts; Mark Gontsarik; Andrea Lassenberger; Jules D. P. Valentin; Aline Wolfensberger; Silvio D. Brugger; Mahsa Zabara; Wouter Pronk; Stefan Salentinig (Advanced Materials Interfaces, 2023)
Abstract The prevention of microbial infections is a global challenge. Efficient antimicrobial coatings that rapidly kill microorganisms upon contact can help minimize their transmission. However, their scalable synthesis is challenging. This work demonstrates the scalable synthesis and characterization of self‐disinfecting nanofilms for the postmodification of hospital‐relevant surfaces. Their antimicrobial action is based on charge interactions between a supercharged cationic surface film and the negatively charged bacteria membrane. Photoinitiated bulk polymerization of an air‐dried [2‐(methacryloyloxy)ethyl]trimethylammonium chloride film on cotton (gowns), nitrile rubber (protective gloves), and glass surfaces (tables, screens) is used for their supercharging, and studied with streaming potential measurements. A 6 nm thick coating dominated by cationic quarternary amine groups is shown by a combination of spectroscopic imaging ellipsometry and X‐ray photoelectron spectroscopy. Antimicrobial in vitro evaluation of the coated surfaces demonstrates up to ≈4 log reductions in bacterial populations in less than 5 min. Confocal laser scanning microscopy and live‐dead staining confirm the surface‐induced killing of bacteria. The coating's range of compatible materials and its rapid bactericidal activity can combat the surface transmission of bacteria and may help to contain the spread of infectious diseases. Its synthesis in environmental conditions is promising for integration into industrial processes.